Analisis Estetika Puisi Berbasis Nama Siswa Kelas Tinggi Sekolah Dasar : Aesthetic Analysis of Poetry Based on the Names of Upper Grade Elementary School Students - Ingke Varamita Datu Karaeng; Muhammad Hanafi; Jumiati Jumiati; Yusma Yusma (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2026)
Literature learning in elementary schools plays an important role in developing students' creativity, language sensitivity, and emotional expression. One effective literary activity to foster these abilities is writing poetry. This study aims to describe the aesthetic elements in name-based poems written by upper-grade students at UPT SD Negeri 10 Otting, particularly in figures of speech, diction, and rhyme. The study used a descriptive qualitative approach, with data drawn from 41 name-based acrostic poems written by students in grades IV, V, and VI. Data were obtained through documentation, observation, and interviews, and analyzed through the stages of reduction, presentation, and conclusion drawing. The results showed that students' poems were dominated by figures of speech (jaja), such as comparison, affirmation, metaphor, and personification, with hyperbole and simile as the next most frequent figures. The diction used tended to be simple and communicative, dominated by abstract, emotive, and motivational words that reflected the students' experiences and world, with limited use of figurative and religious diction. Furthermore, in terms of rhyme, students generally use assonance (repetition of vowel sounds) that occurs naturally, although it is not yet consistently structured or in a fixed pattern. These findings indicate that the name-based acrostic technique effectively encourages students' creativity, self-expression, and awareness of aesthetic language in training literacy skills, especially in reading, writing, and understanding language meaning.